Materials and the Environment : Eco-informed Material Choice. - Ashby, M. F. (Elsevier Science, 2012)
Addressing the growing global concern for sustainable engineering, Materials and the Environment, 2e€is the only book devoted exclusively to the environmental aspects of materials. It explains the ways in which we depend on and use materials and the consequences these have, and it introduces methods for thinking about and designing with materials within the context of minimizing environmental impact. Along with its noted in-depth coverage of material consumption, the material life-cycle, selection strategies, and legislative aspects, €the second edition includes new case studies, impo.